Time to exhaustion during severe intensity running: response following a single bout of interval training - James, D. V.; Doust, J. H. (European Journal of Applied Physiology, 2000)
The primary aim of this study was to examine any change in performance caused by a fatiguing interval training session (TS). A secondary aim of this study was to examine the change in oxygen uptake (VO2) during moderate and severe intensity running, and the relationship with the change in performance. Seven male runners [mean age 24 (SD 6) years, height 1.79 (SD 0.06) m, body mass 67.9 (SD 7.6) kg, maximal oxygen uptake (VO2max) 4.14 (SD 0.49) l · min-1] were studied. The VO2 during moderate and severe intensity running and running performance were studied immediately prior to, 1 h following, and 72 h following TS. The TS was performed on a treadmill, and consisted of six bouts of 800 m at 1 km · h-1 below the velocity at VO2max (vVO2max), with 3-min rest intervals. Performance was also assessed at 1 km · h-1 below vVO2max, in the form of time to exhaustion (tlim). The VO2 and heart rate (fc) were assessed both during the severe intensity performance trial, and the moderate intensity run at 50% vVO2max. Whilst a significant change was observed in running performance and the VO2 during both moderate and severe intensity running prior to and following TS, no relationship was observed between the magnitude of change in these variables. At 1 h following TS, tlim had decreased by 24%, VO2 during moderate intensity running had increased by 2%, and the difference in VO2 between 2 min 45 s and the end of severe intensity running had increased by 91% compared with values recorded prior to TS. At 1 h following TS, ƒc had also increased significantly during moderate intensity running by 5% compared to the value recorded prior to TS. These findings demonstrated that TS resulted in a reduction in performance, and that the relationship between running performance and VO2 during running may be altered under conditions of prolonged fatigue.